A Critique on the Book Studies on Iconology, Humanistic Themes in the Art of Renaissance by Erwin Panofsky - Atefeh Amiri; Zeinab Saber; Nahid Abdi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Studies in Iconology, Humanistic Themes in the Art of the Renaissance by Erwin Panofsky clarifies the function of the Iconology method in interpreting artworks. The goal of this critic is to express the significance of interdisciplinary studies and also is a survey in how methodically organized studies is used in analyzing artworks. Thus this study criticizes and studies the form and contents in the book and also author’s opinions about analyzing and referring to the sources according to Iconology method. In its form, the book looks into the basic relations between the form and subject in analyzing art forms and shows analyzing and interpreting artworks according to their historical context in which they originated and the multiplicity of visual and textual sources which refers to the artworks. By the way, in some cases missing references are seen and the order in using them in the text is not also correct and reliable references are needed, especially sources of Islamic philosophy which have caused some limitations in using the book in some related conditions. Despite these problems, researchers can go further than a mere Formal study by using interdisciplinary and in order to make an understanding about Symbolic Meaning and Contents of artworks, they can have fruitful research.